The Mechanism Of Safety Leadership And Psychosocial Safety Climate On Safety Citizenship Behavior (A Study On The Logistics Industry In Indonesia) - Faidal Faidal; Ria Sakinah (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of safety leadership and psychosocial safety climate on safety citizenship behavior, using safety climate as a mediator. Using a quantitative explanatory approach, data were collected from 142 employees of PT SILOG Group through proportionate stratified random sampling. Data analysis used PLS-SEM with SmartPLS 3.0. The results showed that safety leadership and psychosocial safety climate had a significant positive effect on the formation of safety citizenship behavior. However, safety leadership, psychosocial safety climate, and safety citizenship behavior did not significantly influence safety citizenship behavior. This indicates that in the logistics sector, safety tends to be defined as formal compliance rather than voluntary participation.